A new species of Namtokocoris Sites (Hemiptera: Naucoridae) from Thailand - Vitheepradit, Akekawat (Zootaxa, 2017)
A new species of Namtokocoris was collected from the near-vertical rock surface of Krating Waterfall in Chanthaburi Province, Khao Khitchakut National Park in the eastern region of Thailand. This discovery brings the number of described species of this genus to seven. This species can be diagnosed by the lanceolate median process of the pygophore and a curved aedeagus without a hook in the male, and the straight posterior margin of mediosternite VI, slightly convex posterior margin of the subgenital plate (mediosternite VII) and weakly-developed lobe on the costal margin of the right hemelytron in the female. Illustrations of the new species including a habitus photograph, ecological notes, and diagnostic comparisons among congeners are provided.